Crk adaptor protein promotes PD-L1 expression, EMT and immune evasion in a murine model of triple-negative breast cancer. (2nd January 2018) - Kumar, Sushil; Davra, Viralkumar; E. Obr, Alison; Geng, Ke; L. Wood, Teresa; De Lorenzo, Mariana S.; Birge, Raymond B.
ABSTRACT: The tumor infiltration of immune cells in solid cancers can profoundly influence host antitumor responses. In recent years, immunotherapeutic regimens, that target immune checkpoints, demonstrated significant antitumor response by increasing intra-tumoral immune cell populations, including CD8+ effector T cells. However, administration of such immune checkpoint inhibitors is largely inefficacious in inducing immunogenicity and treating breast cancer. Currently, there is a great need to better understand cell autonomous mechanisms of immune evasion in breast cancer to identify upstream therapeutic targets that increase the efficacy of immunotherapy. Here we show that Crk, an SH2 and SH3 domain-containing adaptor protein implicated in focal adhesion signaling, cell migration, and invasion, and frequently up-regulated in human cancers, has an important role in regulating the tumor immune microenvironment. Using a murine 4T1 breast adenocarcinoma model of spontaneous metastasis in immune-competent BALB/C mice, we show that genetic ablation of Crk by CRISPR-Cas9 leads to enhanced anti-tumor immune cell populations, cytotoxic effector and immune surveillance cytokines in primary tumor. Pathologically, this leads to a significant reduction in tumor growth and lung metastasis. Mechanistically, Crk KO suppresses EMT and PD-L1 expression on tumor cells and acts additively with anti-PD1 therapy to suppress tumor growth and metastasis outcomes. Taken together, these data reveal a previously un-described function of Crk adaptor protein expression in tumor cells for cell autonomous regulation of tumor immune microenvironment.